Posterior crossbite - treatment and stability - Renato Rodrigues de Almeida; Marcio Rodrigues de Almeida; Paula Vanessa Pedron Oltramari-Navarro; Ana Cláudia de Castro Ferreira Conti; Ricardo de Lima Navarro; Henry Victor Alves Marques (University of São Paulo, 2012)
Posterior crossbite is defined as an inadequate transversal relationship of maxillary and mandibular teeth. Even when eliminating the etiologic factors, this malocclusion does not have a spontaneous correction, and should be treated with maxillary expansion as early as possible. This treatment aims at providing a better tooth/skeletal relationship, thereby improving masticatory function, and establishing a symmetrical condyle/fossa relationship. Should posterior crossbite not be treated early, it may result in skeletal changes, demanding a more complex approach. Additionally, an overcorrection expansion protocol should be applied in order to improve the treatment stability. Although the literature has reported a high rate of relapse after maxillary expansion, the goal of this study was to demonstrate excellent stability of the posterior crossbite correction 21 years post treatment.